If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1w + 9 = -31 Reorder the terms: 9 + -1w = -31 Solving 9 + -1w = -31 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1w = -31 + -9 Combine like terms: 9 + -9 = 0 0 + -1w = -31 + -9 -1w = -31 + -9 Combine like terms: -31 + -9 = -40 -1w = -40 Divide each side by '-1'. w = 40 Simplifying w = 40
| 2.5x=5x-3-x | | a+3=12-10 | | 7x+5(x-12)=12 | | f(x)=-6x^5+9x^4-12x^3-15 | | (19x-7)+(6x-12)= | | 3(x+4)=4(3+21) | | -4=0.5p-7 | | 6y+2-y=6+4y-10 | | 3x+7x-30=12+50+20x | | h(x)=16x^2+65x+5 | | ln(11X-3)=0 | | 2x+5=6x+8 | | 35-37=8 | | 3.8n-13=1.4n+15 | | b-12=-16 | | -9x+24=80-2 | | 12a-4b-15a+b= | | 7+2[n-5]n=3.6 | | 9ac+6a= | | g+-2.5+7=4 | | f(x)=x+8ln(3x) | | b^2-b-20=20 | | -7n=70 | | 5xy^2-3x+2y^2+7x+13xy^2= | | 97-9x=-47 | | 10x^2+6x=4 | | 11x+39=x-61 | | (8)n=48 | | 8k-5k=2-6+6k+1 | | a-18=-15 | | 64-8k=72 | | 4x(3x-7)-19x^2= |